Ejercicio de las funciones empresariales por parte de los socios en las cooperativas agrarias - Salazar Terreros, Idana; Galve Górriz, Carmen (REVESCO. Revista de Estudios Cooperativos, 2010)
The aim of this work is to analyse how the coordination of the agrarian cooperative firm is brought about by the members. Said coordination has been analysed by means of a study of the functions which members have to develop in their role as managers. These functions have been numbered; theoretically described, and analysed by using a sample of agrarian cooperatives belonging to the Domination of Origin Qualified Rioja. From the principal results obtained, we can highlight the fact that, in most cases analysed, formal control is exercised under the democratic principle, “one-man-one-vote”; where little delegation of management activities exists in professional management and when this delegation occurs, the cooperative does not obtain higher efficiency levels. The organisation of activities shows evident specialization in the first stages of the production cycle and a high sales concentration. Finally, the selection of personnel is made by the appropriate qualification levels required in each department.